The stuff you can't bottle : advertising for the global youth market - Adz, King, 1969- (London : Thames & Hudson, 2013)
In the networked, multimedia era of Internet 2.0, the only way for advertisers and brands to connect with the notoriously difficult youth market is to get involved with the cultures and subcultures that make up their world. Here, King Adz shares his unique insight into the lives of young people across the globe. His research has taken him to skate parks, clubs, gigs, music festivals and street art events in Europe and North America, Brazil, Russia, China, India, Hong Kong, South Africa and beyond. In each location, he has talked to young people to find out what really fires them, and he has talked to the advertising creatives who have succeeded in connecting with them. No one can predict what youth will be into next month, but this book shows how creatives can grab its attention, build a relationship and crack the market.
Includes index.
Includes bibliographical references and index.
Keywords: Advertising; Marketing; Subculture; Target marketing; Young adult consumers; Young adults -- Attitudes; Young adults -- Conduct of life; Young consumers